2023
DOI: 10.1073/pnas.2300861120
|View full text |Cite
|
Sign up to set email alerts
|

Both long-term grasslands and crop diversity are needed to limit pest and weed infestations in agricultural landscapes

Thomas Perrot,
Adrien Rusch,
Sabrina Gaba
et al.

Abstract: Increasing landscape heterogeneity has been suggested to be an important strategy to strengthen natural pest control in crops, especially through enhancing the amount of seminatural habitats. Increasing crop diversity is also a promising strategy to complement or replace seminatural habitat when seminatural habitat is scarce. However, their relative or possibly interactive effects on pest and weed infestation remain poorly investigated, and the role of different types of seminatural habitats has been understud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 67 publications
0
0
0
Order By: Relevance
“…The NBS in the model is the preservation and restoration of SNHs, that is, grasslands and hedgerows. Scholars have shown that SNH proportion increases the abundance of natural enemies and ultimately supports pest mitigation (Albrecht et al, 2020;Bengtsson et al, 2019;Perrot et al, 2021Perrot et al, , 2023. However, in our data, hedgerows and grasslands are highly correlated (Pearson test: 𝜌 = 0.63).…”
Section: Case Studycontrasting
confidence: 52%
“…The NBS in the model is the preservation and restoration of SNHs, that is, grasslands and hedgerows. Scholars have shown that SNH proportion increases the abundance of natural enemies and ultimately supports pest mitigation (Albrecht et al, 2020;Bengtsson et al, 2019;Perrot et al, 2021Perrot et al, , 2023. However, in our data, hedgerows and grasslands are highly correlated (Pearson test: 𝜌 = 0.63).…”
Section: Case Studycontrasting
confidence: 52%